Whole‐Genome Regulation for Yeast Metabolic Engineering. Issue 2 (18th November 2019) - Jiang, Shuangying; Si, Tong; Dai, Junbiao
Abstract: As the most thoroughly investigated eukaryotic microorganism, Saccharomyces cerevisiae is widely used as a cell factory for producing valuable compounds. Currently, strain construction and optimization still cost a vast amount of capital and time to achieve industrially relevant parameters. To efficiently excavate the genetic factors required for desired traits, many high‐throughput genome engineering tools are developed. This review focuses on the genome‐wide approaches that are applied in yeast. Through multiplex genome editing and/or transcription regulation, these tools generate cell populations with great genetic diversity, enabling identification of the critical factors and synergistic interactions in a short time. Abstract : As a practical workhorse for the production of valuable biochemicals, budding yeast is a hot target of metabolic engineering. Various multiplex, genome‐wide engineering approaches are developed to reduce the time and cost to make yeast cell factories. Here, these approaches are classified into four categories: RNA interference–based methods; oligo‐based methods; clustered regularly interspaced short palindromic repeats–based methods; and recombinase‐based methods.